Acculturation, maternal cortisol and birth outcomes in women of Mexican descent - D’Anna, Kimberly L. (2012)
OBJECTIVE: This study investigated the effects of acculturation on cortisol, a biological correlate of maternal psychological distress, and perinatal infant outcomes, specifically gestational age at birth and birth weight. METHODS: Fifty-five pregnant women of Mexican descent were recruited from a community hospital and collected saliva samples at home over 3 days during pregnancy at 15–18 (early), 26–2 (mid), and 32+ (late) weeks gestation and once in the postpartum period (4–12 weeks). These values were used to determine the diurnal cortisol slope at each phase of pregnancy. Mothers also completed an acculturation survey and gave permission for a medical chart review to obtain neonate information. RESULTS: Multiple regression analyses determined that greater acculturation levels significantly predicted earlier infant gestational age at birth (R(2)=0.09, p=0.03). T-tests revealed that mothers of low birth weight infants weight (<2500g) had significantly higher acculturation scores than mothers of infants with birth weight >2500g (t=−2.95, p=0.005). A blunted maternal cortisol slope during pregnancy was also correlated with low birth weight (r=−0.29, p=0.05), but not gestational age (r=−0.08, p=0.59). In addition, more acculturated women had a flatter diurnal cortisol slope late in pregnancy (R(2)=0.21, p=0.01). Finally diurnal maternal cortisol rhythms were identified as a potential mediator between increased acculturation and birth weight. CONCLUSIONS: This study associated increased acculturation with perinatal outcomes in the US Mexican population. This relationship may be mediated by prenatal maternal diurnal cortisol, which can program the health of the fetus leading to several adverse perinatal outcomes.